Vpliv procesnih parametrov pri postopku thixocasting na mikrostrukturo zlitine AlSi7 - Rudolf, Rebeka (Kovine zlitine tehnologije, 1997)
Thixocasting is used to manufacture some Al alloys with special properties. With this process the undesired dendritic morphology of primary crystals changes to spheroidal. The obtained alloys are used for high pressure casting,die forging, manufacture of composites, etc. For composite manufacturing the influence of process parameters (temperature and stirring velocity) on the size and shape of the spheroidal grains was investigated. The paper deals with the microstructure analysis of AlSi7. The results show a strong influence of the mechanical stirring velocity and temperature in the semisolid on the spheroidal microstructure of primary alpha crystals. The microstructure also depends on the cooling velocity from semisolid to room temperature.
Keywords: livarstvo; tiksotropija; zlitine; aluminij; aluminum; silicij; mikrostruktura